Pulsating flow pressure measurement system with remote acquisition via WiFi - Matias Herrera; Gerardo Martin Imbrioscia; Agustin Lacomi; Pablo Caron (Revista Elektrón)
Peristaltic pumps are devices that deliver flow through the action of rollers compressing an internal flexible tube, resulting in a pulsating flow at the outlet. To measure the flow delivered by such a pump, an orifice plate measurement system was used, which correlates the pressure drop measured before and after the plate with the amount of fluid. To achieve device calibration, it is necessary to understand the dynamic response of the pressure transducers. Therefore, a pressure measurement and recording system was designed and built, which can also control the pump’s rotation speed. This system includes different preset tests that the user can select and execute autonomously. The recorded values are transmitted via a WiFi protocol to the data storage module, providing the equipment with operational versatility.